Engineering Geological Characteristics of Construction Area of Section 5 Yogyakarta-Bawen Toll Road, Magelang, Indonesia - Abrar, Mifthahul; Tamado, Daniel; Indrawan, I Gde Budi (Journal of Applied Geology, 2024)
This paper presents the results of engineering geological mapping conducted in Losari (Central Java), where the Section 5 of the Yogyakarta-Bawen toll road and tunnel will be constructed. This research aimed to evaluate the characteristics of the geomorphology, lithology, and geological structure for assessment of potential geological hazards during and after the toll road and tunnel constructions. This research was conducted by collecting geomorphological and geological data by surface mapping and surface rock engineering properties by laboratory testing, which were not done in the previous site investigation. The surface mapping results show that the study area is at the geomorphological units of steep and gentle slope volcanic hills. The study area consists dominantly of tuff and tuff breccia units. At the surface, the rocks are extremely weathered. The geological structures controlling the study area are extension joints with northwest-southeast and northeast-southwest orientation, consistent with the morphological alignment. Although the study area consists dominantly of hilly morphology and extremely weathered rocks, landslides are rarely observed. This may be attributed to the land use and relatively high friction angle of the soils resulted from weathering of pyroclastic rocks comprising this area. The soils may, however, be susceptible to remoulding. Therefore, cut slopes made for road and tunnel constructions are suggested to be designed to prevent change in the soil state.